A Critique of Shabrangnameh: The Story of Rostam and White Demonś Son - Sajjad Aydenloo (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Shabrangnameh is one of the heroic poems after Shahnameh which is proceeded to take a revenge of Shabrang, the son of White Dave, from Iranians and his battles with Rostam and Iranians. Although the identification and introduction of the work goes back about a hundred and twenty years ago, knowledge and available studies about it are very scarce and its edited text has also recently been published. Shabrangnameh, the poet of which is unknown, has 2877 lines, and it is estimated that it goes back to the sixth century poets. Because this poem is the reference of two courses of the tendency epic literary topics in the Persian Literature PhD program, in this paper, while introducing edition of this book and designing the hints to determine the probable date of its composition, some proposals have been also presented about a part of cases of introduction and recordings of its text.